Campursari Karya Manthous: Kreativitas Industri Musik Jawa dalam Ruang Budaya Massa - Wadiyo, Wadiyo; Haryono, Timbul; R.M. Soedarsono, R.M. Soedarsono; Ganap, Victor (LP2M ISBI Bandung, 2012)
ABSTRACTManthous’s Campursari is a blend of Javanese gamelan pentatonic music with popular music in Indonesia which is based on Western diatonic music. The tones of gamelan and the frequencies of the tune are all transformed into diatonic tone frequency. However, the harmonization which is used is pentatonic harmony of Javanese gamelan. Manthous’s Campursari has succesfully become one of the major music industries since it is supported by three components, namely the organizers of the music productions, the current distribution of music productions, and the needs of the community. The role of mass media is also very helpful toward the existence of this work. News about Manthous’s and his Campursari spread out widely to the public through the mass media. In a relatively short time of its emergence, Manthous’s Campursari has become a mass cultural Javanese music.Keywords: Campursari, mass culture, music industryABSTRAKCampursari karya Manthous adalah sebuah campuran dari musik pentatonik gamelan Jawa dengan musik populer di Indonesia yang mengacu padaMusik diatonis Barat. Nada gamelan dan frekuensi lagu semuanya ditransformasikan menjadi nada frekuensi diatonis. Namun, harmonisasi yang digunakan adalah harmoni pentatonis gamelan Jawa. Campursari karya Manthous telah berhasil menjadi salah satu industri musik besar karena didukung oleh tiga komponen, yaitu penyelenggara produksi musik, distribusi produksi musik, dan kebutuhan masyarakat. Peran media massa juga sangat membantu terhadap keberadaan karya ini. Berita tentang Manthous dan Campursarinya menyebar secara luas di masyarakat melalui media massa. Dalam waktu kemunculannya yang relatif singkat, Campursari karya Manthous telah menjadi musik Jawa dalam ruang budaya massa.Kata kunci: Campursari, budaya massa, industri musik